2021
DOI: 10.1038/s41598-021-90242-2
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of glucose oxidase within gold converts it to a general monosaccharide-oxidase

Abstract: We report that entrapping glucose oxidase (GOx) within metallic gold, expands its activity to become an oxidase for monosaccharides that do not have a natural enzyme with that activity—fructose and xylose—and that this entrapment also removes the enantioselectivity, rendering this enzyme capable of oxidizing the “wrong” l-enantiomer of glucose. These observations suggest that in this biomaterial adsorptive interactions of the outer regions of the protein with the gold cage, pull apart and widen the tunnel betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…The slope of the absorbance fitted line (Fig. 5a) of free GOx (y = 0.003x + 0.225) and GOx-ALG-NCs (y = 0.003x + 0.340) was found to be similar, indicating that entrapped enzyme had similar catalytic activity as free GOx enzyme [43]. Figure 5b exhibited the effect of different pHs on the relative activity of enzymes in GOx-ALG-MCNPs.…”
Section: Protein Structure Ability/enzyme Activity Assaymentioning
confidence: 87%
See 1 more Smart Citation
“…The slope of the absorbance fitted line (Fig. 5a) of free GOx (y = 0.003x + 0.225) and GOx-ALG-NCs (y = 0.003x + 0.340) was found to be similar, indicating that entrapped enzyme had similar catalytic activity as free GOx enzyme [43]. Figure 5b exhibited the effect of different pHs on the relative activity of enzymes in GOx-ALG-MCNPs.…”
Section: Protein Structure Ability/enzyme Activity Assaymentioning
confidence: 87%
“…The yield of the prepared system: GOx-ALG-NCs, MCNPs, GOx-MCNPs, and GOx-ALG-MCNPs were 70. 43 The entrapment efficiency of insulin in the GOx-ALG-MC-NPs was low to MCNPs because of the entrapment of dual protein GOx-ALG-NCs and insulin. The entrapment of multiple components slightly increases the size.…”
Section: Entrapment Efficiencymentioning
confidence: 99%
“…In an earlier report 11 , we have shown that the entrapment of GOx within a 3D metallic matrix of gold, enables the extension of its activity to fructose, xylose and L-glucose, apparently due to conformational changes that open the channel leading to the two active sites of this dimeric protein. That preliminary observation pointed out to the possibility that the active site of GOx, if the right conditions are found to expose it by removing penetration restrictions, has the potential to operate any desired sugar molecule, including saccharides that lack a natural speci c oxidase.…”
Section: Introductionmentioning
confidence: 87%
“…Finally, 40 mg of zinc granules were added, and the reaction mixture was stirred overnight at room temperature. The rest of the procedure was exactly as mentioned above 11 .…”
Section: Methodsmentioning
confidence: 99%
“…The most studied GOx from Aspergillus niger (AnGOx) has been reported to have 270 times lower activity on d -xylose than on d -glucose. 8 Previously, the oxidation of d -xylose with AnGOx was achieved using an excessive amount of enzyme 9 or entrapping it with metallic gold, 10 which is costly for industrial processes. Many sugar dehydrogenases also have the capacity to oxidize d -xylose at the C1 position and have been used for the development of d -xylose biosensors or the production of d -xylonate.…”
Section: Introductionmentioning
confidence: 99%